KONSELING KELOMPOK TEKNIK BEHAVIOR CONTRACT MENGURANGI GEJALA-GEJALA KECANDUAN SMARTPHONE - Tera Pertiwi Atiqoh; Sugiyo (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2020)
The purpose of this study was to determine the effectiveness of the behavior contract technique group counseling to reduce the symptoms of smartphone addiction. This type of research is an experimental study with a one group pretest-posttest design. The sampling technique was purposive sampling. The data collection instrument used was the smartphone addiction scale. Validity was tested with the Product moment formula and with a reliability coefficient of 0.936. The data analysis technique used percentage descriptive analysis and Wilcoxon test analysis. Based on the results of the Wilcoxon test (Z = -2.366, p <0.05), it showed that there was a significant decrease in the symptoms of student smartphone addiction after being given treatment, the average decrease was 18.18%. This shows that the behavior contract technique group counseling is proven to be effective in reducing the symptoms of smartphone addiction in students. Furthermore, school counselors can apply and develop group counseling with the behavior contract technique as an alternative strategy to reduce the symptoms of student smartphone addiction.